Clinical and Epidemiological Characteristics of Streptococcus suis Infections in Catalonia, Spain - Díez de los Ríos, Javier; Reynaga, Esteban; García-Gonzàlez, Merce; Càmara, Jordi; Ardanuy, Carmen; Cuquet, Jordi; Quesada, Maria D.; Navarro, Marian; Vilamala, Anna; Párraga-Niño, Noemi; Quero, Sara; Romero, Alba; et al. (Frontiers in Medicine, 2021)
Introduction: Streptococcus suis (S. suis) is a human zoonotic pathogen of occupational origin, with infection acquired through contact with live pigs or pig meat. Pig farming is one of Catalonia’s biggest industries and as a result this region of Spain has one of the highest density pig populations per km2. The aim of our study was to describe the infections caused by S. suis occurring in that area over a nine-year period. Materials and methods: A retrospective, multi-centre study was carried out by searching records from 15 hospitals in Catalonia for the period between 2010 and 2019. Results: Over the study period altogether 9 cases of S. suis infection were identified in 5 hospitals, with 5 of these cases occurring in the 2018-2019 period. The mean age of patients was 48 ± 8.9 years and all of them were males. Five patients (55.6%) worked in pig farms. The most frequent manifestation of infection was meningitis (5 cases; 55.6%) followed by septic arthritis (3 cases; 33.3%). None of the patients died at 30 days; nonetheless, 4 developed hearing loss as a long-term complication. Conclusions: The most commonly identified S. suis infection was meningitis. Over 50% of the episodes occurred in the last 2 years and have affected pig farm workers. Further surveillance is needed in order to know its prevalence.